Peningkatan Kesadaran Generasi Muda terhadap Bahaya Narkoba melalui Kegiatan Sosialisasi Preventif di Masyarakat - Akmal; Sitti Amninah; Juliani; Musliadi (INKAMKU : Journal of Community Service, 2026)
Drug abuse is a serious problem that has a wide impact on the health, social, and moral aspects of society, especially among the younger generation who are vulnerable to environmental influences. Preventive efforts through outreach activities are an important strategy in raising awareness and forming an attitude of rejection towards drug abuse. This community service activity aims to: (1) increase public knowledge regarding the types and dangers of drugs; (2) raise awareness to avoid drug abuse; and (3) encourage the active role of the community as a prevention agent in their surrounding environment. The implementation method of the activity includes an initial observation stage to identify partner needs, interactive outreach and counseling, and evaluation to measure the level of understanding of participants. The results of the activity showed an increase in participants' understanding regarding the dangers of drugs, which was marked by the ability to identify types of narcotics, understand their negative impacts, and show a change in attitude to be more vigilant towards drug distribution. In addition, this activity also encouraged the formation of collective awareness in prevention efforts in the community. Thus, outreach on the dangers of drugs has proven effective as a preventive measure in building community resilience against the threat of drug abuse